Inflation Targeting at 20 : Achievements and Challenges - Roger, Scott (IMF Working Papers; Working Paper ;, 2009)
This paper provides an overview of inflation targeting frameworks and macroeconomic performance under inflation targeting. Inflation targeting frameworks are generally quite similar across countries, and a broad consensus has developed in favor of "flexible" inflation targeting. The evidence shows that, although inflation target ranges are missed frequently in most countries, the inflation and growth performance under inflation targeting compares very favorably with performance under alternative frameworks. Inflation targeters also tentatively appear to be coping better with the commodity price and financial shocks in 2007-2009 than non-inflation targeters. Key issues going forward include adapting inflation targeting to emerging market and developing countries, and incorporating financial stability issues into the framework.